Electrical Contact Mechanism of Front Electrode Using Bi-Based Glass Frit in Si-Solar Cell - Ae Kim, In; Il Gu, Sin; Soon Shin, Hyo; Hun Yeo, Dong; Yong Jeong, Dae (Asian Journal of Chemistry, 2014)
The front electrode of a solar cell must form an ohmic contact through the etching of the antireflection coating layer of a Si-wafer and glass frit helps the formation of an ohmic contact in the materials of the front electrode of a solar cell. Some studies have reported on the sintering mechanism of glass frit at the front electrode of a solar cell, but this has not been clearly investigated through experiment. Therefore, this study investigated the sintering mechanism of glass frit by the fabrication of Ag pastes to be applied to the front electrode of a solar cell by using glass frit commercially available in the electronic material field as well as by seeking glass frit conditions that allow efficient etching of the antireflection coating. The study found that Bi-based glass frit cause significant changes in contact resistance with variation of the etching degree of the SiNx layer in relation to the composition and amounts added. When the B composition’s added amount was 2.5 vol % among the Bi-based glass frit, it allowed sufficient etching of the SiNx layer. On the contrary, when the added amount was over or below, surface resistance increased.